Improving Students' Ability to Write Descriptive Text By Using Numbered Heads Together (NHT) - Abdul Rabbi Arrasul; Muhammad Ibnu Umair (English Education Study Program, 2020)
The purpose of this research is to determine whether using Numbered Heads Together (NHT) can improve students’ ability to write descriptive texts at SMPN 6 Toili Barat. This research uses quasi-experimental research that requires a post-test for both groups. The research population was eighth grade students of SMP 6 Toili Barat. The sample of this research was class VIII A as an experimental class and consisted of 26 students while class VIII B was a control class and consisted of 27 students. The test consisted of pre-test and post-test. Data were analyzed statistically. After being analyzed, the result of t-counted was 6,744 with a degree of freedom 51, and a significance level of 0,05, t-table was 1,675. Therefore, the t-test result is higher than the t-table. It means that the hypothesis of this research can be accepted. The result showed that there was a significant influence in using Numbered Heads Together to improve students’ writing abilities in descriptive text in eighth grade at SMPN 6 Toili Barat Keywords:Improving; Writing; Descriptive Text; NHT.